Stakeholder views on addressing challenges to the implementation of social prescribing in the United Kingdom - Rafiei, Sima; Honary, Mahsa; Mezes, Barbara (Frontiers in Health Services, 2024)
ObjectivesThis study aimed to understand the key barriers to successfully implementing Social Prescribing (SP) initiatives from different perspectives.MethodsAn in-depth process evaluation using a multi-method qualitative design was conducted. Qualitative data was collected via semi-structured interviews (N = 23) and Focus Group Discussion (FGD’ N = 4). Twenty-three stakeholders took part in the study, including community support providers (n = 7), SP link workers (n = 6), service users (n = 6), NHS employees/referrals, and those who were involved in SP leadership and coordination (n = 4). MAXQDA Version 20.0 was used for management and data analysis.ResultsWe identified eight themes representing challenges for a successful implementation of a SP programme. The themes included (i) financial issues and sustainability, (ii) human resources challenges, (iii) partnership working challenges, (iv) inadequate and inconsistent implementation, (v) information system challenges, (vi) referral system issues, (vii) training and knowledge gaps, and (viii) accessibility and privacy concerns.ConclusionStudy findings provide insight for commissioners, providers, and link workers to guide the delivery of appropriate SP services by identifying a range of factors that hinder the successful implementation of the programme. Future policy, service development, and research should consider tackling these challenges and generating different ideas for potential solutions to address the root causes of problems.